Miejsce wizerunku obszaru i sposoby jego kształtowania w planach strategicznych jednostek samorządowych województwa dolnośląskiego - Nawrocka, Elżbieta (The Importance of an Area Image and Means for its Shaping in Strategic Plans of Self-Government Units in the Lower Silesia Region, 2006)
The objective of the hereby article is to answer the question: whether and what way the shaping of an area image in a tourist market is planned in selected self-government territorial units of the Lower Silesia region. The diagnosis of documents of strategic nature was applied. Additionally, developmental strategies were analyzed in detail (representing defined scenarios) of particular districts in a given region, since the development of tourism and promotion of a district are listed among public tasks of over--commune nature. 12 self-government units of this kind were selected for the research, which define tourism as an uplifting factor of development or an important area of local economy. The results of documentation studies present that the process of creating positive and original image of selected administrative units is hampered by two reasons: - firstly, because it has not been precisely defined, - secondly, not enough attention is paid to identify creation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 689-697